Non-invasive biomarkers for brain aging: the role of autophagy-related microRNAs in plasma exosomes - Qian Cheng; Shuyi Yu; Zhikang Cui; Hang Chen; Jing Fan; Qian Yu; Yan Jin; Yunshan Wang; Ming Li; Zhiming Lu (Frontiers in Molecular Neuroscience)
AimThis study aimed to identify autophagy-related microRNAs (miRNAs) in plasma exosomes as non-invasive biomarkers for brain aging and explore their potential to improve early detection of age-associated neurodegeneration. With the increasing incidence of neurodegenerative disorders, such as Alzheimer’s disease (AD), frontotemporal dementia (FTD), and Parkinson’s disease (PD), non-invasive diagnostic tools are urgently needed.MethodsPlasma samples were collected from 200 individuals, divided into three groups, including young (20–40 years), middle-aged (41–60 years), and elderly (> 60 years). Exosomes were isolated, followed by small RNA sequencing (sRNA-seq) to identify differentially expressed miRNAs, and differentially expressed miRNAs related to autophagy were validated using quantitative real-time PCR (qRT-PCR). Spearman correlation analysis was performed to assess the relationship between autophagy-related miRNAs and brain aging biomarkers. Receiver operating characteristic (ROC) curve analysis was conducted to evaluate the diagnostic performance.ResultsNine autophagy-related miRNAs were identified and validated as significantly upregulated in plasma exosomal from elderly, including hsa-miR-2110, hsa-miR-18a-3p, hsa-miR-766-3p, hsa-miR-4446-3p, hsa-miR-4667-5p, hsa-miR-4433b-3p, hsa-miR-146a-5p, hsa-miR-423-5p, and novel_260. These miRNAs were validated by qRT-PCR. Correlation analysis showed that several of these miRNAs, such as hsa-miR-2110 and hsa-miR-766-3p, were strongly correlated with NfL (r = 0.68, p = 0.002), Aβ42 (r = 0.62, p = 0.004), and p-Tau181 (r = 0.55, p = 0.008). ROC curve analysis showed that combining these miRNAs with NfL resulted in an area under the curve (AUC) of 0.92, outperforming NfL alone (AUC = 0.85) and miRNAs alone (AUC = 0.84). Further subgroup analysis revealed that multiple miRNAs, such as miR-2110, miR-4446-3p, and novel_260, achieved high AUCs (>0.83) in distinguishing middle-aged adults (41–60 years) from older adults (>60 years), supporting their potential utility for early detection of age-associated neurodegeneration.ConclusionThis study identifies a set of autophagy-related miRNAs as promising biomarkers for brain aging. The combination of these miRNAs with traditional biomarkers offers a non-invasive and highly sensitive method for early detection of brain aging, providing significant potential to enhance diagnostic accuracy in neurodegenerative diseases.